Political Communication, Twitter-Diplomacy and Political Violence in Nigeria: Criminalizing the Covid democracy or what? - Ogunseye Inioluwa Iyanu; Ayantayo Temitope Oluwafemi (Universitas Medan Area, 2022)
Man is a relational being. In his dealings with others, he seeks to maximize his association and satisfy his various needs. The torrents of Globalization, diplomacy, social norms, the new media, and popular representation are omnipresent instruments that may determine, control, interpret, and shape the various institutions of governance, public policy, and the conduct of international relations by heads of states and government across borders even in the era of the ‘covid-19 new normal’. It will also show that the Twitter ban is harmful to maintaining a friendly relationship between Nigerian citizens, involvement in governance, and the country's democratic progress. The main purpose of this study is to examine how essential Twitter is for the survival of democracy in Nigeria during Covid-19. This paper argues that Sustainable Democracy does allow for active participation of interested citizens in the state of affairs of the country with citizen involvement and Mobilization via Twitter. This is reflected in the opinions, perceptions, and reactions of people in the 21st Century- Knowledge diplomacy, in an outburst against the Twitter Post of President Muhammadu Buhari on June 2, 2021. The researchers used the conflict theories of political systems and human needs. Secondary data sources were used in the study. The Paper concluded that revolutions in technology are not a hindrance to good governance, and democratic dispensation can only continue for as long as leaders can tolerate public dissension, and media scrutiny and embrace the positivity and uniqueness of media power in politics according to rule of law.